LEAPS of faith- exploring development and implementation of a longitudinal curriculum focusing on mental health, leadership, altruism,ethics and EDI, Professional Identity Formation for medical and dental students - Komal Atta; Tazmeen Kaukab; Fatima Amin; Ahmad Atta (Journal of University Medical & Dental College, 2024)
Abstract In the ever-changing healthcare scenery of Pakistan, demands on health professionals extend far beyond clinical proficiency. These include ethical integrity, effective leadership, care for mental well being and respect of equity, diversity and inclusion. The LEAPS (Leadership, Ethics, Altruism, Professionalism/professional identity and Study skills/patient safety) module is a pioneering educational framework designed for MBBS and BDS students in Pakistan. Structured in a longitudinal fashion, spanning four years, LEAPS boasts of culturally relevant best practices, Sustainable Development Goals (SDGs), and resilience-building strategies to nurture empathetic, culturally competent, and resilient healthcare practitioners. This article outlines the inception, innovative structure, and transformative impact of the LEAPS curriculum.